The Effect of Experimental Methods on Science Ability in Children Aged 5-6 Years in Paud Mawar Unpatti, Nusanive District, Ambon City - Hermelina Abarua (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine the effect of experimental methods on science skills in early childhood at PAUD Mawar UNPATTI, Nusanive District, Ambon City. This research was conducted at PAUD Mawar Unpatti, Nusanive District, Ambon City. Nusanive District, Ambon City, the population in this study was 25 children aged 5-6 years. The sampling in this study was based on the opinion of Sugiyono (2008: 118) the sample is a part of the whole and the characteristics possessed by a population. The sampling method in this study was simple random sampling technique. The samples used in this study were 20 children aged 5-6 from a population of 25 children aged 5-6 years. Data is collected through observation and documentation. The technique used to process and analyze research data is the dependent test. Because the t formula is used, the t formula varies widely and its use is adjusted to the characteristics of the data to be differentiated. There are several requirements that must be fulfilled before the t test is carried out. Research concludes thatFirst. The effect of the lecture method on increasing science learning ability before using the experimental method in children aged 5-6 years at PAUD Mawar UNPATTI, Nusanive District, Ambon City. This is evidenced in the distribution of scientific abilities in preschool children before using the lecture method which is in the range of scores from 0 to 100 and the lowest score is 10, the highest score is 18 with the average value being 15.25.Second.There is an effect of the experimental method on increasing the ability to learn science after using the experimental method in children aged 5-6 years at PAUD Mawar UNPATTI, Nusanive District, Ambon City. This is evidenced by the distribution table of scientific abilities in early childhood children after using the experimental method which is in the range of scores from 0 to 100 and the lowest score is 12, while the highest score is 21, obtained an average of 17.65.Third.Based on the hypothesis test calculation, namely tcount = -105,25 < ttable = 2,146 at α = 0.05 and degrees of freedom n-1 = 20-1 = 19. Thus it can be concluded that the Alternative hypothesis (H1) is accepted and the hypothesis (Ho) is rejected